Perioperative Management of Systemic Lupus Erythematosus Patient with Perianal Abscess Complication due to Trauma - Nasution, Huwainan Nisa; Rahmawati, Lita Diah (Buletin Farmatera, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease that can damage organs and cells due to autoantibodies and immune complexes bound to tissue. Infection is a major source of co-morbid in patients with SLE. The infection has been the second major cause of death in SLE, after disease activity itself. Perianal abscess is part of anorectal abscess which can occur in patients that have a risk factor of trauma on the anorectal region. Management of the patient consists of non-operative and operative procedures. In SLE patients that undergo the operative procedure, it is necessary to do perioperative preparation to prevent post-operative complications such as "flare-up" condition due to SLE. Evaluation of medicines and adjustment of glucocorticoid dosage based on the risk of surgery is important in perioperative preparation.